Reforma al régimen civil con respecto a la causal novena de divorcio, en beneficio y conservación del núcleo familiar amparado en la Constitución de la República del Ecuador - Chamba Iñiguez, Dayanna Valeria (2018)
The present thesis titled: "Reform to the civil regime with respect to the ninth grounds for divorce, for the benefit and conservation of the family nucleus protected in the Constitution of the Republic of Ecuador," makes reference to the grounds for abandonment for divorce as a form of dissolution of the matrimonial bond valid in the Civil Code, theme that is presented as a social problem that includes a set of consequences and affects the attainment of the family and in a special way to the children, aspects for which within this investigation are considered as objectives, to elaborate a conceptual, doctrinaire and legal analysis about the time to start the litigious divorce due to the grounds for abandonment and its effects on the family, as well as to demonstrate the need to extend the base time until one uninterrupted year, in the grounds for abandonment, also determines which rights are violated with this legal provision about the family. On the other hand, it has been proposed to carry out a project to reform the Civil Code to guarantee the protection of the family with the conditions in favour of the attainment of the family nucleus as provided in Article 67 of the Constitution of the Republic of Ecuador, increasing the term to start a litigious divorce due to the grounds for abandonment; for which the following hypothesis was proposed: the minimum time of six uninterrupted months as grounds for divorce, does not guarantee the attainment of family goals, and generates psychosocial effects on children. The present investigation served to obtain the necessary guidelines that demonstrate the need to guarantee the protection and attainment of the family, fundamental pillar in the society, besides guaranteeing the rights of the children and adolescents, because the family has come corrupting more and more, instead of being conserved and promulgated for the purposes destined as such.